Aqidah Akhlak Learning Method at MTsN Triwarno, Kutowinangun District, Kebumen Regency - Eliyanto Eliyanto; Maskub Maskub (LPPM IAINU Kebumen, 2019)
This study aims to determine the learning method of aqidah morals at MTsN Triwarno, Kutowinangun District, Kebumen Regency. This research is descriptive qualitative research. Collecting data using interviews, observation, and documentation. This research concludes that: (1) The method used in learning aqidah morals at MTs N Triwarno, Kutowinangun District, Regency Kebumen includes lecture methods, question and answer, reading, giving assignments, writing, group work, and uswatun jasanah (exemplary); (2) Results of the methods which is used in learning aqidah morals at MTs N Triwarno District Kutowinangun Kebumen Regency is effective and relevant in its implementation. Thing This can be proven and seen from various sides, among others, can be seen from the level good learning completeness, this is indicated by the results of students' daily tests and grades satisfactory student report cards.